ANALYTICAL DESCRIPTION OF THE CURVE CYCLIC LOAD OF CARBON STEEL - Vakulenko, I. O. (Science and Transport Progress, 2009)
In the article the research results of mathematical description of curve of cyclic loading of carbon steel are presented.